Strategy for Developing Aquaculture Villages in East OKU Regency - D Irawan; Y Sari; Fifian Permata Sari fifi; Novayanti Novayanti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
East OKU Regency, located in South Sumatra, is one of the largest catfish producers through pond cultivation. Recently, the Ministry of Marine Affairs and Fisheries designated East OKU Regency as a center for catfish farming, a status formally recognized by officials from South Sumatra and East OKU Regency. The catfish cultivation village spans 1,200 hectares and produces 30 tons annually. To ensure sustainable and environmentally friendly aquaculture practices, and to enhance fish farmers' incomes, effective development strategies are necessary. This research explores strategies for developing aquaculture villages in East OKU Regency. The study employs a case study method, focusing on Belitang District as a representative example of an aquaculture village in South Sumatra Province. A simple random sampling method was used to select 90 farmer groups from a population of 900 fish farmers. The research data were processed and analyzed using SWOT analysis to identify strategies for advancing fish farming villages in East OKU Regency. The findings suggest that the optimal development strategy (SO Strategy) involves providing training and skills related to technology and production systems to boost catfish output. Additionally, strengthening cultivator group institutions is crucial for facilitating the adoption of product quality standards and improving production quality to meet market demands.